Attitudes towards Uncertainty and Randomization: An Experimental Study - Wendelin Schnedler; Adam Dominiak (Verein für Socialpolitik, 2010)
Individuals exhibit a randomization preference if they prefer random mixtures of two bets to each of the involved bets. Such preferences provide the foundation of various models of uncertainty aversion. However, it has to our knowledge not been empirically investigated whether uncertainty-averse decision makers indeed exhibit such preferences. Here, we examine the relationship experimentally. We find that uncertainty aversion is not positively associated with randomization preferences. Moreover, we observe choices that are not consistent with the prevailing theories of uncertainty aversion: a non-negligible number of uncertain-averse subjects seem to dislike randomization.
Keywords: C91; D80; D01; 330; uncertainty aversion; randomization preference; ambiguity; Choquet expected utility model; maxmin expected utility model; experiment